Cholelithiasis associated with haemolytic-uraemic syndrome - Kejariwal, Deepak (Baishideng Publishing Group Co., Limited, 2006)
Cholelithiasis occurs infrequently in the paediatric age group. Hereditary spherocytosis, sickle cell anaemia and thalassemia are the haemolytic disorders most commonly associated with development of gall stones in paediatric age group. The question is whether an isolated episode of haemolysis can cause gallstones.